Isolation technology : - Coles, Tim (CRC Press, 2004)
The second edition of this invaluable text is an updated source of information for both experienced and beginning professionals worldwide. Drawing on his vast experience in this field, the author provides practical ways to improve product standards, increase operator productivity, efficiency, and safety, and cut costs. He discusses setting up clean rooms and techniques for maintaining sterility and includes case studies, resource listings, and numerous photographs. Topics include technology, transfer methods, design specifications and control systems, project proposals, operation methods, and regulatory affairs.